PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEADS TOGETHER UNTUK MENINGKATKAN PARTISIPASI DAN PRESTASI BELAJAR ( Studi Pada Mata Pelajaran Matematika Siswa Kelas V SDN 11 Lahat ) - Nispa Kurniati (UNIB Press, 2020)
The purpose of this study is to describe the application of the number heads together (NHT) learning method to increase student participation and achievement. This research uses classroom action research, which is followed by quasi-experiment. The subjects of the study were students of class 5A in semester 2 of the 2019/2020 school year in SD Negeri 11 Lahat, while for the experiment were students in grade 5B and grade 5C in SD Negeri 11 Lahat. Data collection techniques using assessment sheets and tests. Analysis of the data of this study uses the average (mean) and t test The results of the study show that the application of the cooperative learning model type Number Heads Together (NHT) not only increases student learning participation but also increases understanding of the material and this has the effect of increasing the results of student learning achievement. PTK taking techniques by observation and tests, while the experimental class only tests the Number Heads Together (NHT) learning model. Based on the analysis of this research data, that the application of the Number Heads Together (NHT) learning model can increase participation and mathematics learning achievement of 5th grade students at SD Negeri 11 Lahat.